IDENTIFIKSI POTENSI EKOWISATA DESA BAHOI KECAMATAN LIKUPANG BARAT KABUPATEN MINAHASA UTARA - Walansendow, Agustinus; Adrah, Merry; Mangambea, Natasya C. (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2023)
Tourism is a multisectoral industry which linked to several aspects of life such as social, economic, cultural, political, and environment. The development of industrial world which increasingly depends on tourism sector has made tourism as the so called future industry. Tourism is a driving force and major factor in accelerating the development of a country.This research aims to identify and explain the potential of ecotourism in Bahoi Village, West Likupang District, North Minahasa Regency using descriptive qualitative research methods and data analysis techniques that result in data discovery in the field through interviews with 10 informants, documentation, observation, and literature study.The results showed that Bahoi Village, West Likupang District, North Minahasa Regency has ecotourism potentials, such as: (1) mangrove forests (2) white sand beaches (3) marine protected areas (4) 8 types of seagrass (5) 32 types of coral reefs (6) various types of fish (7) marine mammals and (8) water snails.